Prognostic Prediction, Immune Microenvironment, and Drug Resistance Value of Collagen Type I Alpha 1 Chain: From Gastrointestinal Cancers to Pan-Cancer Analysis - Liu, Yi; Xue, Jinmin; Zhong, Maoxi; Wang, Zhi; Li, Jie; Zhu, Yuxi (Frontiers in Molecular Biosciences, 2021)
Background: Gastrointestinal cancer patients might experience multiple primary tumors in the digesting tract. Therefore, identifying the potential biomarker can help us better understand the underlying mechanism. By searching the GEO database, 4 profiles of gastrointestinal cancer were available for the screening process, and 6 hub genes were found by bioinformatics analysis. Collagen type I alpha 1 chain (COL1A1), one of the hub genes, is a component of the extracellular matrix, and critical for tumor microenvironments. However, it remains unclear that the expression level, signal pathway, prognostic prediction, and immunological value of COL1A1 in multiple cancers. Methods: We comprehensively analyzed gene expression and genetic alteration patterns of COL1A1 among 33 types of malignancies from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression projects. Besides, we explored the correlation of COL1A1 with cancer prognosis, immune infiltrates, PD-L1, tumor mutational burden (TMB)/ microsatellite instability status (MSI), pathway and drug sensitivity analysis of co-expressed genes. Results: The results showed that COL1A1 was highly expressed and associated with poor prognosis in the majority of cancer. The most common alteration type of COL1A1 was missense mutation. And, COL1A1 was associated with poor prognosis in KIRP, LGG, MESO, SKCM, and STAD. For the immunologic significance, COL1A1 expression was closely related to high TMB in THYM, LAML, ACC, KICH, PRAD, and LGG. And, High MSI was observed in TGCT, MESO, PRAD, COAD, SARC, and CESC. In addition, COL1A1 was positively correlated with the abundance of CAFs, macrophages, and tumor-infiltrating lymphocytes. However, it was negatively correlated with CD8+ T cells mainly in CESC, HNSC-HPV+, and SKCM. Besides,as a component of the extracellular matrix, COL1A1 was involved in the activation of epithelial-mesenchymal transition (EMT), , and high expression of HTRA1 was resistant to multiple drugs. Conclusion: COL1A1 can serve as a prognostic and immunological biomarker in multiple cancers.